5G networks: Will technology and policy collide?. (September 2018) - Frias, Zoraida; Pérez Martínez, Jorge
Abstract: Despite being still under development, it is envisaged that 5G networks will provide a 'fibre-like' experience to mobile users. As such, they are expected to accommodate services with very different requirements in terms of latency, bandwidth and reliability, among others, for the vertical sectors. However, the European Union has just approved the Telecommunications Single Market Regulation, which enshrines the network neutrality principle and guarantees that ' all traffic through the Internet is treated equally '. This article explores the potential conflict between net neutrality regulation and future 5G services, particularly regarding network virtualisation. We present a discussion on the challenges of building net neutrality upon judgements on whether traffic optimisation is objectively necessary. This proves complex in a technological environment that envisions network ' slices' created and priced on-demand according to the Quality of Service (QoS) required by specific applications at any given time. In addition, we argue that the 'anything-as-a-service' paradigm might turn into an important source of innovation for the future Internet infrastructure layer, and thus for the ecosystem as a whole. Highlights: 5G networks are expected to accommodate services with very different requirements, among others, for the vertical sectors. The EU has just approved the TSM Regulation aiming to guarantee that ' all traffic through the Internet is treated equally '. 5G will face the challenges of a framework that builds net neutrality around whether optimisation is 'objectively' necessary. 5G architecture might turn into an important source of innovation for the future Internet ecosystem.